Application of Data Mining Correlation Between Family Socio-Economy And Student Achievement Level - Sany Lubis, Fauzan Al An; Buaton, Relita; Sembiring, Hermansyah (Yayasan Bina Internusa Mabarindo, 2024)
Learning achievement is the result of an achievement by students after going through the process of teaching and learning activities. Several factors influence student achievement, one of which is the family's socio-economic environmental factors. The family environment is very influential in the formation of children's character and also the child's mindset. The socio-economic level of the family has an influence on the success of children in achieving academic achievement. This study aims to determine the correlation between family socio-economic and student achievement at SMP Negeri 11 Binjai using the a priori method where this method helps the school and parents to more easily find out what factors are most dominant in influencing family socio-economic correlations to student achievement. From the 20 data tested, the best rule was obtained, namely if the parents of students with junior high school education worked as entrepreneurs and had an income of between IDR 1,000,000 - IDR 1,999,000. Then the student is not in the top 10 in his class with a supporting value of 10% and a certainty value of 100%